Weaving and designing of textiles - Ridenour, Jennie Florence (My University, 1904)
Introduction: The earliest form of clothing used by man was leaves and coats of skin, and these rude garments form the basis for the textile fabrics of all future generations. They represent the two types of fibers used in the manufacture of textiles. The leaves represent our vegetable fibers used in the making of our cotton and linen cloth. While our woolens, formed from animal fiber, are direct descendants of the coats of skin. The fig leaves, used for clothing in primitive times also represents the food of the silk worm from which we obtain that form of animal fiber which gives us our silken tissues.
Citation: Ridenour, Jennie Florence. Weaving and designing of textiles. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Textiles; Textile Design; History of Textiles; Textile Materials; Textile Processing; Clothing; Theses